Synthesis and Antioxidative Properties of 1,2,3,4-Tetrahydropyridine Derivatives with Different Substituents in 4-Position - Daniele Aiello; Hendrik Jonas; Anna Carbone; Daniela Carbone; Camilla Pecoraro; Luisa Tesoriere; Jens Köhler; Bernhard Wünsch; Patrizia Diana (Molecules, 2022)
Natural products are an excellent source of inspiration for the development of new drugs. Among them, betalains have been extensively studied for their antioxidant properties and potential application as natural food dyes. Herein, we describe the seven-step synthesis of new betalamic acid analogs without carboxy groups in the 2- and 6-position with an overall yield of ~70%. The Folin–Ciocalteu assay was used to determine the antioxidant properties of protected intermediate 21. Additionally, the five-step synthesis of betalamic acid analog 35 with three ester moieties was performed. Using NMR techniques, the stability of the obtained compounds towards oxygen was analyzed.